Gender and sex bias in prevention and clinical treatment of women’s chronic pain: hypotheses of a curriculum development - Moretti, Chiara; De Luca, Enrico; D’Apice, Clelia; Artioli, Giovanna; Sarli, Leopoldo; Bonacaro, Antonio (Frontiers in Medicine, 2023)
This discursive paper focuses on undergraduate medical education’s role in tackling gender bias in clinical practice, specifically preventing and managing from a non-biomedical perspective chronic pain in women. A preliminary web search of medical schools’ curricula was performed to identify programs content related to gender bias in pain management. The web search included 10 universities’ websites selected from the top 10 rankings QS Universities Rankings 2022 for medical schools. Additionally, a questionnaire was sent to all deans of the selected academic institutions to explore the curriculum content further. The web search, and the lack of response from the deans, highlighted that relevant curriculum components on gender bias and chronic pain needed to be implemented. Therefore, this paper introduces an innovative curriculum development approach designed by the multi-professional research team to be implemented in medical school programs. This novel educational strategy could also cross-contaminate other healthcare practitioners’ university programs and, thus, stimulate an interprofessional debate into fostering inclusiveness and equal opportunities in health.